Crisis, Resources and the State: Executive Politics in the Age of the Depleted State. (26th February 2013) - Lodge, Martin
Abstract : Questions regarding the problem‐solving capacity of the state have been long‐standing. The financial crisis as well as future demographic and environmental challenges have raised the spectre of the depleted state, a state that lacks legitimacy and resources to steer social, economic and political developments. This article considers how a perspective that centres on executive politics can illuminate key debates surrounding the depleted state. It does so in three steps. First, it considers whether the earlier literature on the 'crisis of the state' of the 1970s contributes to contemporary debates. Second, it questions whether the age of 'governance' has come to the rescue, and not just of the challenges outlined by the earlier literature. Third, it discusses the contribution of executive politics to the study of the contemporary state's problem‐solving capacity and draws wider implications of the age of the depleted state for executive politics.